Features of the application of uniform shelterwood felling in pine stands in Polissia, Ukraine - Ткач, В. П.; Жежкун, А. М. (Forestry and Forest Melioration, 2024)
Introduction The uniform shelterwood felling is an important silvicultural measure of close-to-nature forestry. Such felling type was applied in the pine stands in Polissia (forest zone of Ukraine) in small volumes in the past years. In many plots, the felling was not completed, and the cut areas were not sufficiently regenerated with pine and other valuable species. Often felling was carried out in years with poor pine seed production, and measures aimed to promote natural regeneration were not carried out. Therefore, different authors have obtained contradictory data on the success of natural pine regeneration after uniform shelterwood felling, as well as the feasibility of such type of felling. The aim of the study was to determine the specificities of uniform shelterwood felling in pine stands in Polissya zone and to assess the feasibility of their application in the context of close-to-nature forestry. Materials and Methods Active experiments were established in the mature pine stands in Eastern Polissia in Ukraine. The experiments involved different intensities of the first stage of uniform shelterwood felling (10–50%) with a decrease in relative density of stocking to 0.3–0.7 and measures to promote natural forest regeneration. In pine stands on permanent sample plots, trees were divided according to categories of health condition, Kraft classes, and classes of crown length along the trunk. The pine seeds were counted. Accounting for advance growth, self-sowing of tree species, and regeneration success evaluation were carried out on more than 100 plots in pine stands. Results In pine forests of fresh pine forest type with a decrease in relative density of stocking to 0.5–0.6 and natural regeneration assistance for 3–4 years, the pine regeneration was poor or insufficient. In pine stands in fresh oak-pine the relatively poor forest type with medium seed production after the first stage of felling with a decrease in relative density of stocking to 0.4, the pine regeneration was satisfactory. In the pine stands in wet oak-pine forest type with decrease of relative density of stocking to 0.4, the density of 3–4-year-old pine advance growth was 8.8–34.7 thousand stems?ha-1, and in the plots with relative density of stocking of 0.3 it was somewhat smaller (9.1–11.3 thousand stems?ha-1). Natural regeneration there was good and satisfactory. In the plots without assistance in regeneration, the number of pine advance growth was 1.8–4.0 times less and did not reach the standard indicators. In pine stands in fresh hornbeam-oak-pine relatively rich forest type after the first stage of felling, the regeneration was poor or insufficient. In pine stands at wet oak-pine relatively rich forest type, with a reduction of relative density of stocking to 0.5 and the laying of furrows, natural regeneration was satisfactory. After the second (final) stage of uniform shelterwood felling more than 79% of the pine advance growth survived, of which 58% were undamaged. Conclusions The natural regeneration after uniform shelterwood felling was the most successful in fresh and wet oak-pine relatively poor forest types. Felling should be carried out in years of good pine seed production, in stands with well-developed crowns, the length of which is at least one third of the height of the trunk, and poor cereal vegetation in the above-ground cover as well as undergrowth. It is advisable to reduce the relative density of stocking to 0.4 during the first stage of felling. A mandatory precondition for felling is early implementation of measures promoting natural regeneration by means of soil mineralization and preliminary removal of undergrowth. To ensure natural seeding of plots (if necessary) pine seeds should be undersowed. During the felling stages, the damage to the advanced growth of pine and other valuable species should be minimized. 1 Fig., 4 Tables, 23 Refs.